A Simple Position Sensing Device for Upper Limb Rehabilitation - Abdul Rahman, Hisyam; Samuthram, Kesava Naidu; Yeong, Che Fai; Khor, Kang Xiang (International Journal of Integrated Engineering, 2018)
Stroke is a leading cause of disability which can affect shoulder and elbow movements which are necessary for reaching activities in numerous daily routines. Rehabilitation under the supervision of physiotherapists in healthcare settings is to encourage the recovery process. Unfortunately, these sessions are often labor-intensive and limited intervention time between physiotherapist and the stroke patient due to staff constraints. Dedicated robotic devices have been developed to overcome this issues. However, the high cost of these robots is a major concern as it limits their cost-benefit profiles, thus impeding large scale implementation. This paper presents a simple and portable unactuated interactive rehabilitation device for upper limb rehabilitation purposes. This device has been developed by using a conventional mouse integrated with three interactive training modules, namely the Triangle, Square, and Circle modules intended for training shoulder and elbow movements. Results from five healthy subjects showed the more deviation from the path will be happened when the subject move their hand to the other side of their dominant hand. Besides, the shape of the module that includes combination of X and Y axis direction is more difficult compare to either X or Y axis.